2021
DOI: 10.3390/buildings11060227
|View full text |Cite
|
Sign up to set email alerts
|

BIM for Deconstruction: An Interpretive Structural Model of Factors Influencing Implementation

Abstract: Transitioning from demolition to deconstruction practices for end-of-life performances is gaining increasing attention following the need for the construction industry to minimise construction and demolition waste. Building information modelling (BIM) presents an opportunity for sustainable deconstruction. However, the notion of BIM for deconstruction (BIMfD) is still in its infancy in the United Kingdom. Although a few studies on BIMfD are evident, a focus on identifying the underlying factors necessary for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 43 publications
(86 reference statements)
0
13
0
Order By: Relevance
“…The researchers revealed that "lack of faith in the integrity of BIM" and "lack of client demand" among other barriers were one of the factors behind the lack of BIM implementation in Australia [37]. Many researchers in Germany, the United Kingdom, Canada, the United States, Denmark, France, China, Brazil, South Korea, and the Middle East [38][39][40][41][42][43][44][45][46] have also found numerous BIM implementation barriers. It includes lack of BIM experience, investment costs, lack of awareness, lack of specified standards, market and cultural changes, interoperability problems, lack of specific guidelines for BIM implementation, and habitual resistance to change [31,44,47].…”
Section: Bim Implementation Barriers In Global Contextmentioning
confidence: 99%
“…The researchers revealed that "lack of faith in the integrity of BIM" and "lack of client demand" among other barriers were one of the factors behind the lack of BIM implementation in Australia [37]. Many researchers in Germany, the United Kingdom, Canada, the United States, Denmark, France, China, Brazil, South Korea, and the Middle East [38][39][40][41][42][43][44][45][46] have also found numerous BIM implementation barriers. It includes lack of BIM experience, investment costs, lack of awareness, lack of specified standards, market and cultural changes, interoperability problems, lack of specific guidelines for BIM implementation, and habitual resistance to change [31,44,47].…”
Section: Bim Implementation Barriers In Global Contextmentioning
confidence: 99%
“…As further affirmed by [41], the method is useful for fields with few experts and emerging thematic areas to which BIM LCA belongs. Furthermore, the approach has gained widespread adoption in the built sector due to its efficiency in interpreting complex systems [45,46].…”
Section: Barriersmentioning
confidence: 99%
“…"Matrice d'Impacts croises-multipication applique and classment" abbreviated as MICMAC as explained from previous studies such as [42,46], is built on multiplication properties of matrices. It is used in examining by analysis the driving power and dependence power of barriers.…”
Section: Micmac Analysismentioning
confidence: 99%
“…A 3D building model that identifies the clash detection, improves the schedules of construction, and prepares construction site activities was shown to be useful in everyday operations [77]. Additionally, the utilization of BIM has provided significant benefits to the construction industry over the project's life cycle, from conceptualization to demolition [78]. Significant advantages found in the design phase of the project include improved visualization, efficiency, and productivity, whereas, during the construction phase, BIM can consist of cost analysis and auto-scheduling, allowing for improved project coordination and on-time delivery capabilities [79].…”
Section: Building Information Modelling (Bim)mentioning
confidence: 99%